Developing Cooperative Learning Based Module for Teaching Reading to the Second Semester Students at English Department of FKIP UIR - Novitri, Safriani (J-SHMIC : Journal of English for Academic, 2017)
This research is designed to develop the students’ reading comprehension of narrative, descriptive and hortatory exposition texts by using cooperative learning based-module. It aims to explainthe current needs, to design and toexamine the validity and practicality of cooperative learning based-module in developing reading comprehension at the second-semester Students in English Department of FKIP – UIR. The design of this research is R & D approach by using ADDIE model. The sample was selected from second semester students at English Department of FKIP UIR. Five validators involved in evaluating the product to evaluate its the validity, and the practicality. The quantitative data were collected through a questionnaire and test and qualitative data were collected through an interview. To develop the learning material to be givento students, the researcher tried to find out the need analysis, the validity, and the practicality of her product in designing and implementing readingin cooperative learning based-module. Based on the research finding of this research was considered valid and practice and it can be used to develop the quality of students in reading comprehension.